Idling Fuel Consumption and Emissions of Public Vehicles run by Bhaktapur Minibus Sewa Samiti and its Reduction Possibilities - Suwal, Ravi; Ale, Bhakta Bahadur (Journal of the Institute of Engineering, 2019)
This research paper is carried out to analyze the idling fuel consumption and emissions of public vehicles of Bhaktapur Minibus Sewa Samiti (BMSS) and quantify the reduction possibilities of idling emission. In order to reduce the air pollution in Kathmandu Valley, low carbon technology like idling reduction has become necessity. Idling of passenger vehicle is mainly due to waiting for passengers at the bus stops and stopped by traffic. Idling contributes significantly to energy consumption without any useful output. Many researchers found that idling is harmful to engine and increases maintenance. For that, idling data of different routes were collected and fuel consumption were tested using pseudo method. These data were used to calculate the total idling time, fuel consumption, GHG emissions and financial loss in the routes. Idling time was as high as an hour in a trip. About 18% to 32 % of idling time was due to traffic only and the traffic were high at day (11 am – 5 pm) and evening. The idling fuel consumption and GHG emissions were 117.56 ml to 181.16 ml and 0.31 kg to 0.478 kg per trip in the routes of BMSS respectively. Using 3 minutes of limit, the fuel consumption and emissions could be reduced by 22.48 ml to 59.45 ml and 0.059 kg to 0.157 kg per trip respectively. Rs. 943,783 out of Rs. 3,214,872 of financial loss could be saved in selected routes annually.